The Smartphone Uses of Algerian Youth: A Field Study on a Sample of University Students - Dehlas, Gennifer (جامعة أحمد بن بلة وهران 1 - مخبر مخطوطات الحضارة الإسلامية في شمال أفريقيا, 2022)
The study aimed to identify areas of the Algerian youth's use of the smartphone, through a sample of university students, as the researcher followed the methodology of surveying the sample from the university student community, and the researcher adopted the questionnaire as the main tool for collecting study data, as it was applied to 361 respondents from the aforementioned community. After analyzing the data, the study reached the following results: - 93.31% of the sample members own Samsung smartphones. - The study showed that 82% of the sample members use mobile phones in scientific research. - The study arrived at the motives of use of mobile phone by the study sample are ritualistic.
Keywords: الشباب -- طلبة الجامعة -- الدوافع -- الهواتف الذكية -- الجامعات الجزائرية